Re-writing ‘Woman’: New Woman Hybridity in Araki Iku’s “The Letter” and Charlotte Perkins Gilman’s “Turned” - Khou, Carrie (Current Objectives of Postgraduate American Studies, 2012)
Turn-of-the-century (1890-1920) short fiction in Japan and the United States portrays the New Woman as a figure of hybridization subverting the legitimacy of binary gender codes. This article outlines how Charlotte Perkins Gilman’s story “Turned“ and Araki Iku’s “The Letter“ exemplify and interrogate the hybrid nature of the New Woman concept. The concept of hybridity serves to reveal female identity as negotiable and permeable, simultaneously disclosing the New Woman as a transnational figure, which enables a broad set of cultural interpretations.